Length-Weight Relationship, Growth Patterns and Sex Ratio of Dog Conch Strombus Canarium Linnaeus, 1758 in the Waters of Kota Batam - Ramses Ramses; Fauziah Syamsi; Notowinarto Notowinarto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
This study aims to analyze the aspect length of weight relationship, growth pattern, and sex ratio of Dog conch. This research was conducted in May-August 2018. The samples were collected from three locations (stations) which became the main of catching the Dog conch in Kota Batam, namely, Jaloh Island, Kangkung Bay, and Terong Island. A total of 377 individuals (162 males and 215 females) S. canarium were collected from three research stations. The value of the length-weight relationship for females, males, dan blended, at the respective station, are Jaloh Island, W=0,000142L2,924, R²= 0.555 (female), W=0,00049L2,610, R²= 0.566 (male), and W=0,000165L2,881, with a value of R²= 0.572 (blanded); Kangkung Bay, W=0,0850L1,275, R²= 0.325 (female), 0,00000511L3,185, R²= 0.776 (male), and W=0,0384L1,480, with R² = 0.374 (blended); As well as Terong Island, W=1,227L0,746, R²= 0.180 (female), W=0,00139L2,385, R²= 0.714 (male) and W=0,118L1,305 with R²= 0.355 (blended). The pattern of growth of Dog conch is negative allometric (b<3) where long growth is faster than weight gain, except male Dog conch in Kangkung Bay, has a coefficient (b>3) has a positive allometric growth pattern, where weight gain is faster than long increments. The sex ratio of Dog conch on Jaloh Island and Terong Island is balanced, while in Kangkung Bay it is not balanced. Overall the sex ratio in the study location is not balanced with a ratio of 1: 1.33 with the expectation frequency (Ei) of 188.8.